2021
DOI: 10.1186/s13018-021-02653-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish version of the Goodman score in total hip arthroplasty

Abstract: Purpose Currently, patient-reported outcome measures (PROMs) are the standard instruments used to compare arthroplasty results. Goodman et al. recently published a well-constructed scale with excellent psychometric properties that can be quickly administered. The main objective of our study was to translate, culturally adapt, and validate a Spanish version of the Goodman questionnaire in patients who underwent total hip arthroplasty (THA). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The original Goodman study reported a significant moderate correlation with both HOOS and KOSS [6]. In its Spanish validation, a similar correlation was noted with the OHS [7]. Moreover, in knee patients, the KUJALA, KOOS quality of life, and WOMAC scales can predict the Goodman score, yielding an area under the ROC curve of 0.82 (95% CI: 0.70 to 0.94) [9].…”
Section: Discussionmentioning
confidence: 74%
“…The original Goodman study reported a significant moderate correlation with both HOOS and KOSS [6]. In its Spanish validation, a similar correlation was noted with the OHS [7]. Moreover, in knee patients, the KUJALA, KOOS quality of life, and WOMAC scales can predict the Goodman score, yielding an area under the ROC curve of 0.82 (95% CI: 0.70 to 0.94) [9].…”
Section: Discussionmentioning
confidence: 74%
“…The recent development of better instruments to assess satisfaction has enabled researchers to compare more reliable results and establish what satisfaction means for patients [27]. The Goodman scale is reliable and aims to determine satisfaction and patients' self-perceived improvement after TKA [7,18,56].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all patients were asked if they experienced anterior knee pain. The principal outcome of the study was satisfaction and patients' perceived improvement in their quality of life after TKA, using the Goodman scale, which has been validated for TKA and adapted for Spanish speakers [7,18,56]. This scale has two sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a Spanish adaptation and validation of the Goodman score questionnaire were published, reporting higher Cronbach's alpha (0.95) and test-retest ICC (0.87) than those of both the Italian and English versions [36]. Besides cultural and language differences, the higher indices of the Spanish adaptation may be due to the inclusion in the study of patients undergoing THA only, as well as the use of a larger cohort than the one described in the present study.…”
Section: Discussionmentioning
confidence: 99%